Partial auxeticity of laterally compressed carbon nanotube bundles - Korznikova, Elena A. (2022)
Carbon nanotubes (CNTs) have attracted increasing attention because of their enormous potential in various technologies. Herein, the evolution of the structure and elastic properties of a CNT bundle under compression in uniaxial and biaxial regimes is analyzed using a chain model with a reduced number of degrees of freedom. The compression stress–strain curves consist of four stages, each of which is characterized by a specific structure and deformation mechanism. In the first stage, all CNTs have the same cross section; in the second stage, the translational symmetry is preserved in the system, but with a doubled translational cell; in the third stage, CNT collapse takes place, leading to the loss of the translational symmetry; the fourth stage begins when all CNTs collapse. Elastic constants are calculated for the CNT bundle under uniaxial and biaxial compression during the first two stages. In all loading schemes, during the second stage of deformation, the CNT bundle exhibits partial auxetic properties. The results obtained contribute to the fundamental knowledge for the design of carbon nanomaterials with enhanced properties.